2011
DOI: 10.3144/expresspolymlett.2011.69
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative separation of the effect of voids on the static mechanical properties of hygrothermally conditioned carbon/epoxy composites

Abstract: Abstract. The paper investigates the effect of voids and hygrothermal conditions on bending, compressive, and interlaminar shear strength (ILSS) of T300/914 composite laminates. By adopting different autoclave pressures during a cure cycle, specimens with three different void contents ranging from 0.33% to 1.50% were obtained. Experimental results reveal that compressive, bending strength, and ILSS decrease with increasing void contents and immersion time. The most significant decrease in strength of aged spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 17 publications
1
16
0
Order By: Relevance
“…In the literature it is reported that the ILSS is particularly sensitive to void content . As mentioned in Bulk Resin Samples section, the difference in void content among the tested system is believed to be low, and in particular below 1%.…”
Section: Discussion Of Resultsmentioning
confidence: 90%
“…In the literature it is reported that the ILSS is particularly sensitive to void content . As mentioned in Bulk Resin Samples section, the difference in void content among the tested system is believed to be low, and in particular below 1%.…”
Section: Discussion Of Resultsmentioning
confidence: 90%
“…At higher loading, CNTs get closer to each other in the matrix; hence their strong attractive forces might have led them to form agglomerates. These agglomerates can act as stress risers and also increase the free volume by creating voids in the matrix . This phenomenon may contribute to premature matrix failure during loading which results in lower mechanical properties.…”
Section: Resultsmentioning
confidence: 99%
“…8). The other possibility for low tensile strength at high concentration can be the agglomeration of Si-CL particles, which reduces elasticity of polymeric chains in CA [60]. The thickness of the membrane also affects membrane characteristics and mechanical strength; therefore, thickness comparisons of pure and hybrid membranes are combined in Table 2.…”
Section: Tensile Strength Measurementmentioning
confidence: 99%